Impact of illegal building to local authorities / Che Roslan Che Daud - Che Daud, Che Roslan (2012)
Illegal building or unauthorized building is a big problem that faced by most local authorities in Malaysia. In general, illegal building means the building has built without any permission from local authority. In this scenario, illegal building will create many problems to local authority and public. We can see now the illegal building or illegal structure grow like mushrooms after rain on the road reserve and electric lines throughout our country. If there is no awareness and action to be taken by state authorities and local authorities, this will become a big problem that can give a negative impact to local authorities in Malaysia. This research will cover the impact of illegal building to local authorities, the approaches or practice has been used by local authorities to control the illegal building. The research will be focus on approach to control and manage of illegal building in four (4) local authorities in state of Kelantan. With this research, it will help local authorities to improve their management in controlling in case of illegal building. Besides that, most people never thought that illegal building will give a big impact to local authorities and to public. This research also will helps people to understand what means of illegal building and help to reduce the construction of illegal building in the future.